Psychological distress among undergraduates in the northern university of Malaysia: an exploratory study - Mahmud, Wan Mohd. Rusbidi Wan; Mahmud, Wan Zarina Wan (2001)
The main aim of the study is to determine the prevalence of psychological distress and its associated risk factors among undergraduates in the Northern University of Malaysia.A cross sectional survey, involving 468 randomly selected students attending the Health Center for their routine medical check-ups.Psychological distress was assessed using the Malay version of GHQ-12.A score of 3 and above was considered a 'case' in this study.Participants were also given the Student Stress Scale and questionnaires on basic demographic details and various putative risk factors.450 returned completed questionnaires.117 scored 3 and above on the GHQ-12,giving a prevalence rate of 26%. Females were more than twice as likely to be affected (F=35.8%;M= 12.7%).Psychological distress was found to be linked to higher number of life events experienced over the last one year (i< 0.01) and high scores on the Student Stress Scale (i<0.01), presence of any stressor (p< 0.01), and poor relationship with tutors/lecturers (p<0.01).The rate of psychological distress among the undergraduates is 2.5 times higher than the national average. Stress management programs can be an important strategy to enhance their ability to cope with the demands of tertiary education.Regular screening for possible'psychological casualties' and immediate treatment may prevent potential waste of valuable human resources.